Back to the Future
XVI, 323 p.
Keywords: Schools and teachers are facing various challenges in a rapidly changing world. In such circumstances, discussing and sharing concerns of mutual interest regarding policy, practice and research is crucial to creating more sophisticated understandings of the various challenges as a first step in the improvement of education. While the future should not be imprisoned in the past, the past does provide valuable lessons that will undergo new iterations in constructing the future. The future will be multi-faceted and complex and the different chapters included in this book are intended to provide important contributions from which to build the future of education. The different chapters provide readers with international perspectives, frameworks and empirical evidence of legacies, continuities and changes in educational policy, practice and research in teaching, teacher education and learning. We hope that they inspire the readers to build the future and to change their own professional realities. —Cheryl J. Craig, Ph.D., Professor, University of Houston, Houston, TX, USA, Secretary, ISATT This book metaphorically captures the looking backward to the past—pressing forward to the future that typically takes place on celebratory occasions. It causes us to pause and remember even as we race toward a time unknown to us. In a sense, the authors featured in this book serve as tour guides pointing out legacies, continuities and changes in teaching and teacher education. I strongly urge readers not only to peruse the chapters that follow, but to distill them to their essences and to glean what is of value to be learned from them. In conclusion, the ISATT Executive especially thanks the co-editors of this volume who have compiled a superb collection of chapters on a timely and relevant topic.